Song-assisted Genially-based media to improve students’ integrated science and social studies learning outcomes - Tarigan, Ari Anggriani; Sutikno, Putri Yanuarita (Indonesian Journal of Science and Mathematics Education, 2025)
Students' difficulty in understanding Science and Social Studies (IPAS) learning material is due to its nature, which tends to rely on memorisation, while students do not like to memorise. Based on these problems, research was conducted by developing Genially-based learning media assisted by songs. The study aimed to determine the developed learning media's feasibility, practicality, and effectiveness of the developed learning media. The research method used is Research and Development (R and D) based on the Borg and Gall model. This research involved eight stages: potential and problems, data collection, product design, design validation, design revision, product trial, product revision, and trial use. The results showed that song-assisted Genially-based media: (1) was feasible to use by obtaining a score of 90% from media experts and 97% from material experts, (2) practical to use by obtaining teacher response questionnaire results of 97.5% and 99.5% students, (3) quite effective to use by obtaining normality test values, t-tests, and N-gain tests of 0.6935 with medium categories. Song-assisted Genially-based media effectively improve student learning outcomes by making the material more interesting and easily understood. This research implies the need for innovation in developing song-assisted Genially-based learning media according to modern learning needs.